2023
DOI: 10.1089/ars.2022.0200
|View full text |Cite
|
Sign up to set email alerts
|

NRF2 and the Moirai: Life and Death Decisions on Cell Fates

Abstract: Significance: The transcription factor NRF2 (NF-E2-related factor 2) plays an important role as a master regulator of the cellular defense system by activating transcriptional programs of NRF2 target genes encoding multiple enzymes related to cellular redox balance and xenobiotic detoxication. Comprehensive transcriptional analyses continue to reveal an ever-broadening range of NRF2 target genes, demonstrating the sophistication and diversification of NRF2 biological signatures beyond its canonica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 227 publications
2
7
0
4
Order By: Relevance
“…AZD treatment attenuated the expression of Atg-5 and p62 proteins with no alterations in LC3 proteins, again confirming that the autophagic machinery was not involved. Researchers have reported a cross-talk between SIRT1 and Nrf2 associated with cyclin B1 expression [37]. Our study confirmed this observation via the B(a)P-induced activation of SIRT1, Nrf2, and cyclin B1 expression.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…AZD treatment attenuated the expression of Atg-5 and p62 proteins with no alterations in LC3 proteins, again confirming that the autophagic machinery was not involved. Researchers have reported a cross-talk between SIRT1 and Nrf2 associated with cyclin B1 expression [37]. Our study confirmed this observation via the B(a)P-induced activation of SIRT1, Nrf2, and cyclin B1 expression.…”
Section: Discussionsupporting
confidence: 90%
“…Increased oxidative stress has also been shown to elevate Nrf2 levels, leading to the significant activation of GST in vitro and in vivo [39,52]. Nrf2 thus plays a central role in balancing cell homeostasis by balancing the production and scavenging of ROS [37]. Our study demonstrated that AZD treatment attenuated the B(a)P-induced activation of Nrf2 and the induction of the GST detoxification enzyme.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…An appropriate dose of EGCG can activate the NRF2 antioxidant-responsive element pathway to resist any side effects, including DNA damage or cell death. 21,41,42 Our results also demonstrated that ENPs significantly diminish the suppression of body weight and reduce hepatotoxicity and DNA damage; thus, we systematically explored whether the NRF2 pathway is involved in the effect of ENPs. As shown in Fig.…”
Section: Resultsmentioning
confidence: 96%